SEMANTIK AL-QUR’AN TOSIHIKO IZUTSU: RELEVANSI dan KONTRIBUSINYA dalam TAFSIR KONTEMPORER - Muhammad Rusidi (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2025)
This article examines Toshihiko Izutsu’s semantic approach to Qur’anic studies through his works, particularly God and Man in the Qur’an: Semantics of the Qur’anic Weltanschauung, and its relevance to contemporary Qur’anic exegesis. This approach is grounded in the analysis of conceptual meanings in the Qur’an using synchronic and diachronic methods to uncover the semantic world that shapes the structure of Islamic religious thought. Employing a qualitative methodology based on library research and content analysis, this study traces how Izutsu systematically and contextually maps key Qur’anic concepts. The findings reveal that the semantic approach not only opens new avenues for understanding the Qur’anic text but also reconstructs the relationship between revelation and language as a dynamic system of meaning. Through his contributions, Izutsu offers an integrative interpretive paradigm that remains highly relevant to the development of contemporary Qur’anic studies.